2021
DOI: 10.3389/fncir.2021.660837
|View full text |Cite
|
Sign up to set email alerts
|

The Flow of Axonal Information Among Hippocampal Subregions: 1. Feed-Forward and Feedback Network Spatial Dynamics Underpinning Emergent Information Processing

Abstract: The tri-synaptic pathway in the mammalian hippocampus enables cognitive learning and memory. Despite decades of reports on anatomy and physiology, the functional architecture of the hippocampal network remains poorly understood in terms of the dynamics of axonal information transfer between subregions. Information inputs largely flow from the entorhinal cortex (EC) to the dentate gyrus (DG), and then are processed further in the CA3 and CA1 before returning to the EC. Here, we reconstructed elements of the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 128 publications
(179 reference statements)
4
37
0
Order By: Relevance
“…Since axons are more excitable than dendrites or the cell body 22 , 54 , DBS-evoked subthreshold depolarization at the axon is expected to arrive at the soma on a sub-millisecond timescale due to the short chronaxie 15 , 54 , 55 . Furthermore, the observation that spikes did not occur until ~7–8 ms after the onset of individual electrical pulses of 40 Hz DBS further argues against direct antidromic activation of the stimulated neuron, since antidromic spiking typically has a latency shorter than a couple of milliseconds given the axon conduction velocity 56 , 57 . Finally, individual pulses delivered at 140 Hz failed to evoke prominent changes in Vm or spike rate, consistent with the delayed response to DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Since axons are more excitable than dendrites or the cell body 22 , 54 , DBS-evoked subthreshold depolarization at the axon is expected to arrive at the soma on a sub-millisecond timescale due to the short chronaxie 15 , 54 , 55 . Furthermore, the observation that spikes did not occur until ~7–8 ms after the onset of individual electrical pulses of 40 Hz DBS further argues against direct antidromic activation of the stimulated neuron, since antidromic spiking typically has a latency shorter than a couple of milliseconds given the axon conduction velocity 56 , 57 . Finally, individual pulses delivered at 140 Hz failed to evoke prominent changes in Vm or spike rate, consistent with the delayed response to DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneering work by Taylor et al in 2003, advancements in microfluidic technologies have been widely adopted by the neuroscience community for preclinical research [1]. The ability to segregate and integrate neuronal populations across compartmentalized microfluidic chips has facilitated the construction of robust, physiologically relevant model systems for studying neuronal networks in vitro with unparalleled experimental control [2][3][4][5]. However, these platforms do not inherently aid the establishment of feedforward projection sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this we found that most of the DSs were simultaneous in the anterior and posterior dorsal hippocampus. This finding is explained by the fact that the perforant path spreads feed‐forward projections to all parts of the DG (Amaral & Witter, 1989 ; Vakilna et al, 2021 ). Surprisingly, contrary to previous reports (Bragin et al, 1995 ), we found that only a fraction of DSs were bilaterally synchronous.…”
Section: Discussionmentioning
confidence: 99%